PEDAGOGICAL CONDITIONS OF CULTURE FORMATION OF PEDAGOGICAL COMMUNICATION OF FUTURE TEACHERS BY MEANS OF DIALOGICAL LEARNING SITUATIONS - Lysevych, O.V. (Pedagogy of Higher and Secondary Education, 2008)
The present article reveals the problem of organization of forming conditions of the culture of pedagogical intercourse of the future teacher. The author of the article claims that building of dialogue training situation makes for the effective forming of the culture ofpedagogical intercourse.